Андайн шүтлэг бишрэлийн соёлын учир: Cultural Aspects of Dance Rituals - Дархад, Хянган (Mongolian Studies, 2023)
Dance ritual is a valuable intangible culture among Mongolian nationalities. Different cultural traces and types penetrated into the dance rituals of Mongolian ethnics. In this article, the author discusses the cultural rituals of animals, trees, soul, remedies and shamanic worship which included in the dance rituals in ancient Mongolian culture. From the cultural content, dance rituals kept different cultural traces of ancient folklore, literature, songs, dances, medicine, religion, rites, cultural conception and consciousness of the Mongolians. From the scientific aspect, dance rituals has been connected to the studies on art and literature, social and cultural anthropology, ethnology, theology, human and cultural geography, science of medicine so on. Therefore, dance ritual is one general aspect of cultural heritage. Studying the cultural aspects in dance rituals will be significant to the studies on Mongol culture.